Peningkatan Hasil Belajar Matematika Melalui Model Pembelajaran Discovery Learning Dalam Mewujudkan Profil Pelajar Pancasila - Mutmainnah, Nurul; Sahabuddin, Chuduriah; Assaibin, Muhammad; Sukmawati, Sukmawati; Jannah, Miftahul (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2025)
The purpose of this study is to know how to increase the results of student mathematics after the application of the discovery learning model to realize the pancasila student's profile, as for the sample in this study is class vii f of the 4th state junior high school polewali. The kind of study used was class action research (PTK). Research shows that has met previously set success indicators: (1) the percentage of students who achieve sharp increases from 53.12% of the I cycle to 87.5% in the ii cycle, (2) student activity increased from 59.03% with the highly active category of the I cycle to 83.68% with the highly active category of the ii cycle, (3) the study-study-facility increased from 64.81% in the learning cycle I to 79.62% in the category carried out in the ii cycle, And (4) the application of Pancasila student profiles increased from 50,92% with a category not materializing on I cycle to 79.04% with a category materializing on cycle ii. Based on research and discussion, the discovery learning model was able to improve the learning of mathematics and to reflect on the profile of Pancasila student class vii f of public school 4 polewali.